Factores de riesgo prevalentes para fibrilación auricular en pacientes adultos - Avila Cortez, Iván Ricardo (2020)
Atrial fibrillation is the most common sustained arrhythmia in adults and, furthermore, a known risk factor for ischemic stroke and systemic embolism. Often, patients suffering from atrial fibrillation also present comorbidities as risk factors for developing it, such as high blood pressure, heart failure, obesity, previous stroke, type 2 diabetes mellitus, coronary heart disease, etc. Over time, systematic reviews of unique risk factors and meta-analyzes have been carried out, for example for alcohol, C-reactive protein, diabetes mellitus, obesity, physical activity and kidney failure, in relation to the risk of atrial fibrillation. That is why the present work tries to make a statistic of which are the most prevalent risk factors in order to then be able to carry out preventive work that allows us to somehow reduce the cases of atrial fibrillation in our environment. For this reason, it is proposed to demonstrate which are the most prevalent risk factors for atrial fibrillation in Trujillo, of which only 5 were chosen: Type 2 diabetes mellitus, arterial hypertension, advanced age, ischemic cardiomyopathy and hyperthyroidism; having as a database clinical histories of the patients of the Regional Teaching Hospital of said city during the period 2013-2018, fulfilling the selection criteria. During the processing and analysis of the information, the data records that were consigned in the corresponding collection sheets were statistically analyzed using the Chi Square test and processed using the SPSS v.25 software, which were then presented in simple input tables and double, as well as relevance charts.